Modeling of supercritical fluid extraction bed: A critical review - Banafi, Ahmad; Wee, Siaw Khur; Tiong, Angnes Ngieng Tze; Kong, Z.Y.; Saptoro, Agus; Sunarso, J. (2023)
In recent decades, supercritical fluid has gained increasing interest in various industries. One of its promising applications is the extraction of valuable compounds from solid materials such as various plant parts, known as supercritical fluid extraction (SFE). With growing interest to employ SFE commercially, it is vital to provide reliable and robust mathematical modeling for the SFE to optimize the process and achieve maximum extraction yield and to better understand the process mechanism. The present review aims to critically report and discuss different strategies proposed thus far for the mathematical modeling of the SFE process in packed bed columns. The main features, key assumptions and their validity, mathematical expressions, and applications of each modeling strategy are evaluated. Additionally, this manuscript covers a comprehensive review of the different studies carried out for SFE of plant matrices encompassing mathematical modeling part. The studied systems in each research (both solute and solid substrate) along with the employed models as well as the ranges of the operational conditions such as pressure, temperature, and solvent flow rate are also highlighted. This review assists the scientific community to identify the most suitable models and the appropriate operating conditions for different systems in the SFE process.